1972
DOI: 10.1113/jphysiol.1972.sp009926
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic acinar cells: measurement of membrane potential and miniature depolarization potentials

Abstract: SUMMARY1. Intracellular recordings of membrane potentials have been made in vitro from the exocrine acinar cells of the mouse pancreas using glass microelectrodes.2. The mean membrane potential of the acinar cells was -41P2 mV. Spontaneous miniature depolarization potentials of 05-5 0 mV amplitude and occurring at random intervals were often observed superimposed upon the resting membrane potential. Atropine 2-8 x 1O-6M decreased, and physostigmine 1-23 x 10-5 M increased, the frequency and amplitude of the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
47
0

Year Published

1973
1973
1993
1993

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 14 publications
7
47
0
Order By: Relevance
“…Both procedures cause a secondary stimulation PANCREATIC AMYLASE AND Ca SECRETION of amylase secretion, due to the acetylcholine released, but do not directly stimulate the acinar cell to secrete enzymes, or influence the stimulatory effect of CCK-Pz or acetylcholine on these cells. Therefore the small depolarization of acinar cells due to acetylcholine and CCK-Pz (Dean & Matthews, 1972;Petersen & Matthews, 1972;J. R. Greenwell and T. Scratcherd, in preparation), although reflecting an altered membrane permeability, is presumably not responsible for enzyme secretion per se.…”
Section: Discussionmentioning
confidence: 99%
“…Both procedures cause a secondary stimulation PANCREATIC AMYLASE AND Ca SECRETION of amylase secretion, due to the acetylcholine released, but do not directly stimulate the acinar cell to secrete enzymes, or influence the stimulatory effect of CCK-Pz or acetylcholine on these cells. Therefore the small depolarization of acinar cells due to acetylcholine and CCK-Pz (Dean & Matthews, 1972;Petersen & Matthews, 1972;J. R. Greenwell and T. Scratcherd, in preparation), although reflecting an altered membrane permeability, is presumably not responsible for enzyme secretion per se.…”
Section: Discussionmentioning
confidence: 99%
“…The studies were carried out using male white Swiss mice weighing 18-30 g. After decapitation the pancreas was removed and secured to a Perspex platform, which was mounted in a superfusion chamber as described by Dean & Matthews (1972). Superfusion fluid heated to 370 C was pumped through the chamber, which had a volume of 4 ml., at a constant rate of 3.5 ml./min.…”
Section: Superfu8ionmentioning
confidence: 99%
“…Electrophysiological techniques have recently been applied to pancreatic acinar cells as a means of studying the earliest membrane-related steps in stimulus-secretion coupling (Dean & Matthews, 1972;Kanno, 1972;Matthews & Petersen, 1973;Greenwell, 1975). Nishiyama & Petersen (1974 have shown that depolarization induced by cholinergic agonists can be explained as due to an increased membrane permeability to Na+, possibly associated with a smaller increase in the permeability to K+.…”
mentioning
confidence: 99%
“…If we assume (i) that maximal doses of ACh and secretin have a similar quantitative effect on fluid secretion by the ductal epithelium in the intact gland (see Fig. 2) and (ii) that secretin has no effect on acinar cells (even at high doses it does not alter membrane potential or input resistance; Dean & Matthews, 1972;Greenwell, 1975;Petersen & Ueda, 1975) then we can estimate that about three-quarters of the fluid secreted from the intact gland in response to ACh must come from the ducts, whereas only about onequarter will originate from the acini. As duct cells make up 2 % by volume of the rat pancreas, whilst the acini constitute about 90 % (Weaver, Sorenson & Kaung, 1985), the ductal epithelium must secrete (on an equivalent cell volume basis) much more fluid in response to ACh than the acini.…”
Section: Discussionmentioning
confidence: 99%